2021
DOI: 10.1039/d1an01078f
|View full text |Cite
|
Sign up to set email alerts
|

Micro-Raman spectroscopy of lipid halo and dense-core amyloid plaques: aging process characterization in the Alzheimer's disease APPswePS1ΔE9 mouse model

Abstract: The deposition of amyloid plaques is considered one of the main microscopic features of Alzheimer’s disease (AD). Since plaque formation can precede extensive neurodegeneration and the main clinical manifestations of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 72 publications
1
15
0
Order By: Relevance
“…Cell nuclei indicated by the DNA peak can also be detected as elliptical structures surrounding the plaque. The Aβ plaque indicated by the β-sheet peak at 1670 cm –1 is distinguishable from the surrounding tissue and correlates in size and shape to plaques reported in other studies . Yet, cell nuclei also exhibit an elevated intensity compared to the surrounding tissue, which could be attributed to peaks specific for cell nuclei between 1663 and 1690 cm –1 .…”
Section: Resultssupporting
confidence: 62%
See 2 more Smart Citations
“…Cell nuclei indicated by the DNA peak can also be detected as elliptical structures surrounding the plaque. The Aβ plaque indicated by the β-sheet peak at 1670 cm –1 is distinguishable from the surrounding tissue and correlates in size and shape to plaques reported in other studies . Yet, cell nuclei also exhibit an elevated intensity compared to the surrounding tissue, which could be attributed to peaks specific for cell nuclei between 1663 and 1690 cm –1 .…”
Section: Resultssupporting
confidence: 62%
“…Peaks commonly found in biological spectra were chosen for univariate data analysis (Table S1). ,,, Each peak (±5 cm –1 ) was integrated, and results were plotted as 2D heat maps. The consistent narrow interval of ±5 cm –1 was used to ensure comparability of the maps.…”
Section: Methods Sectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main features of RS techniques described in this review, are summarized in Table 1 (Ref. [5,6,[18][19][20][21][22]24,25,27,28,[31][32][33][34][35][36][37][38][42][43][44][45][46][47][48]52,[54][55][56][57][60][61][62][63][64]).…”
Section: Coherent Raman Scattering (Crs)mentioning
confidence: 99%
“…Exploiting these peculiarities, RS demonstrated great potential for the analysis of AD biosamples, such as histologic specimens and biological fluids. Several studies have shown that Raman experiments can allow detection of amyloid plaques and neurofibrillary tangles in unlabelled samples as derived from human brain tissue of AD patients or in animal models, as well as distinguish them from the surrounding areas [18][19][20][21][22]. For example, a Raman study in mice demonstrated the ability to differentiate AD from healthy subjects with an accuracy of 85.9%, identifying distinctive disease-related biochemical alterations in retina samples [23].…”
Section: Introductionmentioning
confidence: 99%